What Is Peace? The Perspective of People with Cognitive Disabilities in Costa Rica - Dotta Brenes, Andrea (2023)
To address the subject of peace, this paper originates from the generative question, ‘What is peace, and how can it be practiced?’ Targeted at the adult population with cognitive disabilities, the study includes students from the Program for the Inclusion of People with Cognitive Disabilities in Higher Education (PROIN) of the University of Costa Rica. The cognitive impairments they experience are deemed to be “mild” or “medium” since they do not hinder the students’ social progression or physical independence. A focus group was conducted with eight people who examined exemplary images (provided in the annexes). The aim was to understand their perception on how visually they differentiate between what is peace and what is not. From this standpoint, discussions on peace, war, and conflict resolution were developed according to the participants’ perspectives. This paper presents the students’ answers and a final reflection on what they consider to be peace through drawings, photos, images, or their hobbies. The study contributes to understanding the participants' perspectives on the topics of interest, how they deal with conflict situations in their daily lives, and how they seek peace in their families and daily environments.